Ecophysiological and Cell Biological Traits of Benthic Diatoms From Coastal Wetlands of the Southern Baltic Sea - Prelle, Lara R.; Albrecht, Martin; Karsten, Ulf; Damer, Pauline; Giese, Tabea; Jähns, Jessica; Müller, Simon; Schulz, Louisa; Viertel, Lennard; Glaser, Karin (Frontiers in Microbiology, 2021)
The German Baltic Sea coastline is characterized by sea-land transitions zones, specifically coastal peatlands. Such transition zones exhibit highly fluctuating environmental parameters and dynamic gradients that affect physiological processes of inhabiting organisms such as microphytobenthic communities. In the present study four representative and abundant benthic diatom strains (Melosira nummuloides, Nitzschia filiformis, Planothidium sp. (st. 1) and Planothidium sp. (st.2)) were isolated from a Baltic Sea beach and three peatlands that are irregularly affected by Baltic Sea water intrusion. Ecophysiological and cell biological traits of the strains were investigated for the first time as function of light, temperature and salinity. The four strains exhibited euryhaline growth over a range of 1 to 39 SA, surpassing in situ salinity of the respective brackish habitats. Furthermore, they showed eurythermal growth over a temperature range from 5 to 30°C with an optimum temperature between 15 and 20°C. Growth rates did not exhibit any differences between the peatland and Baltic Sea strains. The photosynthetic temperature optimum of the peatland diatom isolates, however, was much higher (20-35°C) compared to the Baltic Sea one (10°C). All strains exhibited light saturation points ranging between 29.8 and 72.6 µmol photons m-2 s-1. The lipid content did not change in response to the tested abiotic factors. All data point to wide physiological tolerances in these benthic diatoms along the respective sea-land transitions zones. This study could serve as a baseline for future studies on microphytobenthic communities and their key functions, like primary production, under fluctuating environmental stressors along terrestrial-marine gradients.